Pertimbangan Hakim dalam Menjatuhkan Pidana Mati Terhadap Pelaku Tindak Pidana Turut Serta Melakukan Pembunuhan Berencana (Mimbar Keadilan, 2023)
This study aims to find out the considerations of judges in deciding cases of premeditated murder and to find out the provisions related to capital punishment in the latest law. Premeditated murder is a criminal act that requires law enforcement in the fairest way possible. In Indonesia, perpetrators of premeditated murder are subject to criminal threats in the form of the death penalty or life imprisonment. There are quite a number of cases of premeditated murder that have occurred in Indonesia, one of which is premeditated murder carried out by law enforcement officials, namely the case of the murder of Brigadier J carried out by Ferdi Sambo and his aides. The method used in this study is a normative method using primary and secondary legal materials used to solve the problems that exist in this research. This study presents the results of previous research that has been conducted on capital punishment in Indonesia. The results of the analysis prove that the judge in imposing capital punishment on the defendant must be in accordance with the existing facts and the elements in the statutory regulations.